Incorporación de Espirulina (Spirulina Maxima) en dietas para alevines de truchas arco iris (Oncorhynchus Mykiss) - Pókniak, José (Avances en Ciencias Veterinarias, 2007)
<!–[if gte mso 9]> Normal 0 21 false false false ES-CL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> A nutritional assay was conducted with rainbow trout fry (Oncorhynchus mykiss), from 2 up to 30 g body weight, using a spirulina meal (Spirulina maxima). The spirulina meal was incorporated in the feed at 0,0; 2,5 and 5,0% levels in order to verify the effects on productive performance, mortality (%) and uric acid levels (mg/dl). After 90 days, the productive performance (body weight, feed intake, feed conversion and specific growth rate) was not significantly affected (Pâ‰¥ 0,05) by the presence of spirulina meal in the diets. The mortality was not significantly (Pâ‰¥ 0,05) modified by the treatments, the same was observed in the uric acid levels. Under the experimental conditions used, the results obtained show that a 5% of spirulina meal can be incorporated in the feed for rainbow trout fry.